An exploratory study of the experiences and challenges faced by advanced life support paramedics in the milieu of neonatal transfers - Raisuyah Bhagwan; Pradeep Ashokcoomar (AOSIS, 2021)
Background: The safe transfer of critically ill neonates is important for their survival. This calls for greater preparedness on the part of paramedics to effect these transfers safely. Aim: To understand the experiences and the challenges faced by advanced life support (ALS) paramedics during neonatal transfers. Setting: The study setting consisted of advanced life support paramedics from urban and rural areas in KwaZulu-Natal. It comprised of a network of district hospitals as well air and ground transfer facilities, both public and private. Method: Using a qualitative research approach, the study sought the views of ALS paramedics who were involved in neonatal transfers in KwaZulu-Natal. A purposive sample of n = 8 ALS paramedics was selected. Data were collected using in-depth semi-structured interviews. The data were analysed through the process of thematic analysis. Results: The study found that paramedics faced multiple complex challenges related to neonatal transfers. Poor pre-transfer preparation of the neonate, equipment related challenges, lack of clinical support available during transfers and pressure to effect inappropriate transfers were some of the challenges they faced. These challenges coupled with insufficient education and the lack of sub-speciality programmes to capacitate, rendered them unprepared to deal with neonatal transfers effectively. Conclusion: Emergency medicine needs to provide greater attention towards preparing all stakeholders for successful neonatal transfers. Contribution: The findings provide recommendations for a programme that will limit risks involved with, and support the inter-healthcare facility transfer of critically ill neonates in South Africa.